Thrombin-stimulated immunoprecipitation of phosphatidylinositol 3-kinase from human platelets. - Mitchell, C A (1990)
Growth factors and transforming proteins that activate tyrosine phosphorylation have been shown to cause an increased labeling of 3-phosphate-containing phosphatidylinositols. Turnover correlates with the formation of a complex between phosphatidylinositol 3-kinase, the activated protein-tyrosine kinase, and other proteins thought to participate in transmembrane signaling. When human platelets are treated with thrombin, labeling of 3-phosphate-containing phosphatidylinositols is stimulated with a time course and concentration dependence consistent with a role for these lipids in platelet activation. We now report that when human platelets are stimulated with thrombin, a complex forms between phosphatidylinositol 3-kinase, a protein-serine/threonine kinase, and an uncharacterized platelet membrane protein. The complex is immunoprecipitated from detergent lysates of thrombinstimulated platelets by a rabbit antiserum prepared against a peptide from the cytoplasmic domain of the mouse platelet-derived growth factor (PDGF) receptor. The antigen is not the PDGF receptor, since complex formation is not stimulated by PDGF and thrombin-induced complexes are not precipitated by another rabbit antiserum against the same peptide or by monoclonal anti-human PDGF receptor antibodies. Formation of the complex is rapid (within 30 sec) and occurs at thrombin concentrations that stimulate platelet aggregation and secretion (50% of maximal complex formation at 0.03 unit of thrombin per ml). We propose that the complex initiates formation of 3-phosphate-containing phosphatidylinositols that may function in platelet activation.